A Pengukuran Data Sampel Berat dan Panjang Udang Vaname (Litopenaeus vannamei) Berbasis Citra Digital Menggunakan Metode ChessBoard: Uji homogenitas pada data sampel udang - Zulfaqar; Ananda; Syarif SS, Dadang; Akbar, Memen (Politeknik Caltex Riau, 2024)
Vaname shrimp (Litopenaeus vannamei) cultivation is a prominent aquaculture activity in Indonesia. This study introduces a digital image-based method for measuring shrimp weight and length, enhancing the traditional anco technique. The Chessboard distance method was employed to accurately measure curved objects like shrimp bodies. A homogeneity test assessed whether manual measurement data and pixel-based data for weight and length shared similar variation distributions. For shrimp weight, the F-test yielded a value of 0.000000028, significantly smaller than the critical F value of 0.817796464 at a 5% alpha level, indicating no significant difference in variation between the variables. Similarly, shrimp length data produced an F value of 0.0001174, also below the critical value of 0.8175241. These results confirm that both variables—weight and length—show no significant variation differences between manual and pixel-based methods. The findings validate the digital image-based approach as a reliable method for predicting shrimp size, offering an accurate and efficient alternative for Vaname shrimp measurement.